1994
DOI: 10.1021/j100086a007
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Study of the Interaction of Catechin with .alpha.-, .beta.-, and .gamma.-Cyclodextrins

Abstract: The inclusion complex of catechin with cyclodextrins (CDxs) is examined by the use of l H NMR, UV, and circular dichroism spectroscopies. The UV measurements demonstrate the existence of additional absorbing species of catechin in the presence of P-CDx. The 'H NMR provides evidence for the formation of inclusional complexes between catechin and P-and y-CDxs through changes in the chemical shifts of the proton resonances of catechin and that of the protons inside the CDx activity. The apparent formation constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 5 publications
1
21
0
Order By: Relevance
“…4 will be discussed from the standpoint of the induced chemical shifts of ECg in the presence of β-CD ( Table 2). The proton signals due to H 2 , H 3 , H 6 , and H 8 , of ECg shifted upfield in the presence of β-CD. It has been known that signals due to protons, which do not come into close contact with the atoms on the inner surface of β-CD, tend to shift upfield because of the C-C bond anisotropy effect.…”
Section: Inclusion Complex Of Ecg With β-Cdmentioning
confidence: 97%
See 1 more Smart Citation
“…4 will be discussed from the standpoint of the induced chemical shifts of ECg in the presence of β-CD ( Table 2). The proton signals due to H 2 , H 3 , H 6 , and H 8 , of ECg shifted upfield in the presence of β-CD. It has been known that signals due to protons, which do not come into close contact with the atoms on the inner surface of β-CD, tend to shift upfield because of the C-C bond anisotropy effect.…”
Section: Inclusion Complex Of Ecg With β-Cdmentioning
confidence: 97%
“…5, the exchange of the two H 6 and H 8 protons of GCg in the presence of β-CD was slow in comparison with that of GCg alone. These findings indicated that H 6 and H 8 were difficult to exchange with deuterium because of inclusion of the A ring in the cavity of β-CD in the complex β-CD and GCg.…”
Section: Inclusion Complex Of Ecg With β-Cdmentioning
confidence: 99%
“…The interaction between ferulic acid and ␥-cyclodextrin was investigated in water/solvent by nuclear magnetic resonance spectroscopy, since this technique provides direct and detailed information on the physico-chemical interactions indicative of the formation of an inclusion complex [19][20][21][22][23].…”
Section: H Nmr Studiesmentioning
confidence: 99%
“…The inclusion of CA and EC with native b-CDs has been studied and an inclusion complex with a stoichiometry of 1:1 in solid state and in aqueous solution, was attained [5,13,14]. Furthermore, the probable structures of the inclusion complexes of b-CD with CA and EC have been proposed on the basis of NMR and molecular dynamics simulations [5,13].…”
Section: Introductionmentioning
confidence: 99%